Fidel's Failed Economy - Pascual, Maria Teresa Diokno (Kasarinlan: Philippine Journal of Third World Studies; Vol 14 No 3 (1999): Politics and Governance, 2009)
In 1992, a newly-elected president confidently predicted Asia’s newest tiger by term’s end. President Ramos promised the people high growth, a per capita income of at least $1000, a level playing field, a more efficient and less corrupt bureaucracy and an end to both IMF tutelage and the “boom-bust” growth cycle. None of these took place and Malacañang was very willing to blame the Asian crisis for the Ramos economy’s shortcomings. The more realistic view, according to the author, was that the Ramos economy, because of its dependence on foreign funds and the value of the dollar, stood on shaky ground from the very beginning. Since it did not integrate poverty alleviation in the strategy for economic growth it was not designed to address poverty and social inequality. Being anything but sustainable, the Ramos plan for Asian entigerment sputtered before the president could end his term of office.